2020
DOI: 10.1002/jat.4061
|View full text |Cite
|
Sign up to set email alerts
|

A review on nanotoxicity and nanogenotoxicity of different shapes of nanomaterials

Abstract: Nanomaterials (NMs) generally display fascinating physical and chemical properties that are not always present in bulk materials; therefore, any modification to their size, shape, or coating tends to cause significant changes in their chemical/physical and biological characteristics. The dramatic increase in efforts to use NMs renders the risk assessment of their toxicity highly crucial due to the possible health perils of this relatively uncharted territory. The different sizes and shapes of the nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 301 publications
8
29
0
1
Order By: Relevance
“…In a similar study also when rat cardiomyocytes (H9C2) and human brain fibroblast cells (T98G) were exposed to a 5 mg/mL dose of 30 nm CeO 2 , no major cytotoxicity was observed 28 . Being nontoxic nature of bio-prepared nanoceria could be highly likely attributed to the presence of substantial marine-derive biomolecules covered the surface of nanoparticle boosting their bioactivity and safety toward healthy cells as conformed with several literature reports 19 , 29 .
Figure 9 Cytotoxicity and biosafety of marine-mediated nanoceria (CeO 2 NPs) against healthy L929 fibroblast cells.
…”
Section: Resultssupporting
confidence: 59%
“…In a similar study also when rat cardiomyocytes (H9C2) and human brain fibroblast cells (T98G) were exposed to a 5 mg/mL dose of 30 nm CeO 2 , no major cytotoxicity was observed 28 . Being nontoxic nature of bio-prepared nanoceria could be highly likely attributed to the presence of substantial marine-derive biomolecules covered the surface of nanoparticle boosting their bioactivity and safety toward healthy cells as conformed with several literature reports 19 , 29 .
Figure 9 Cytotoxicity and biosafety of marine-mediated nanoceria (CeO 2 NPs) against healthy L929 fibroblast cells.
…”
Section: Resultssupporting
confidence: 59%
“…In a similar study also when rat cardiomyocytes (H9C2) and human brain fibroblast cells (T98G) were exposed to a 5 mg/mL dose of 30 nm CeO2, no major cytotoxicity was observed 22 . Being nontoxic nature of bio-prepared nanoceria could be highly likely attributed to the presence of substantial marine-derive biomolecules covered the surface of nanoparticle boosting their bioactivity and safety toward healthy cells as conformed with several literature reports 13,23 . The catalytic efficiency of the biogenic CeO2 NPs was studied toward degradation of the organic methylthioninium chloride which is also known as Methylene Blue (MB).…”
Section: Cytotoxic Assay Of Green Ceo2 Npssupporting
confidence: 55%
“…Several studies have also shown an increase in intracellular oxidative stress and damage when cells are exposed to NMs such as carbon nanotubes (Francis and Devasena, 2018), gold nanoparticles (Chen et al, 2009), copper nanoparticles (Meng et al, 2007), titanium NMs (Demir, 2020), etc. These events often lead to adverse effects such as DNA aberration, genetic instability and inflammation depending upon the cell type, nature of NM and material concentration (Demir, 2021).…”
Section: Clinical Studies and Perspectivesmentioning
confidence: 99%